The Inter-Religious Marriage in Islamic and Indonesian Law Perspective - Saepullah, Usep (SCAD Independent, 2019)
The phenomenon of inter-religious marriage is problematic, controversial, and resulted debate among Muslim and non-Muslim relationship in Indonesia. It also not only becomes the social conflict among Muslim and non-Muslim couples, but also pro and contra among the others such as family and society. In the classical Islamic marriage law discourse (fiqh al-munakahat), there are two kinds of inter-religious marriage, namely marriage between Muslim men with non-Muslim women and marriage between non-Muslim men with Muslim women. Some Muslim scholars said that Muslim men allowed marrying non-Muslim women and non-Muslim men prohibited marrying Muslim women, which the reason is based on the concept of polytheists and the group of experts (Kitabiyyah). In contrast, some Muslim scholars in Indonesia rejected inter-religious marriage based on the reason that it has been changed and regulated under Marriage Law Number 1 of 1974 and President Regulation Number 1 of 1991 on Islamic Law Compilation. One the one hand, the phenomenon of inter-religious marriage is an interesting phenomenon in the society and on the other hand it will become the legal implication to the inheritance and children care rights in Islamic and Indonesian law perspective. Therefore, the aim of this paper is to examine comprehensively about the legal status of inter-religious marriage in Islamic and Indonesian law perspective, including its legal implication to the inheritance and children care rights.